AB093. The efficacy of medical treatment of Peyronie’s disease: Potaba monotherapy vs. combination therapy with Tamoxifen, L-carnitine, and PDE5 inhibitor - Park, Jong Jin (Transl Androl Urol, 2016)
OBJECTIVE: This study was designed to evaluate the efficacy of combination therapy of Tamoxifen, L-carnitine and daily PDE5 inhibitors and to compare with Potassium para-aminobenzoate (Potaba) monotherapy in the medical treatment of Peyronie’s disease. METHODS: From January 2011 to December 2014, a total of 104 patients with Peyronie’s disease enrolled in this study. Sixty-eight patients were treated with Tamoxifen 20 mg and Acetyl L-carnitine 330 mg twice a daily in addition to daily PDE5 inhibitors (Tadalafil 5 mg once daily) combination therapy (Group 1), while thirty-four patients were treated with Potassium para-aminobenzoate 12 g daily (Group 2), Pain on erection, impossibility of intercourse, plaque size, penile curvature and IIEF-5 were assessed. Plaque volume was assessed by penile ultrasonography. RESULTS: Both groups showed resolution of pain and intercourse satisfaction after treatment. The pre-treatment plaque sizes of both groups were 17.1±7.2, 17.0±5.0 mm, respectively. After treatment, those parameters significantly reduced to 13.2±5.6, 16.2±5.3 mm. In group 1, combination therapy significantly improved the angle of penile curvature, plaque size, and IIEF (P<0.05). In group 2, the size of the plaque, penile curvature and IIEF were improved after Potassium para-aminobenzoate monotherapy. However, no significant differences were observed. CONCLUSIONS: Statistically significant improvement in intercourse satisfaction, plaque size, degree of curvature and IIEF-5 was observed in combination therapy. Combination therapy may be the more effective than Potassium para-aminobenzoate monotherapy in medical treatment of Pyeronie’s disease.